2018
DOI: 10.11646/zootaxa.4471.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen new species of the spider genus Althepus Thorell, 1898 (Araneae: Ochyroceratidae) from Southeast Asia

Abstract: Sixteen new Althepus species of the spider family Ochyroceratidae are reported from Southeast Asia: A. bamensis Li et Li sp. nov., A. changmao Li et Li sp. nov., A. dongnaiensis Li et Li sp. nov., A. guan Li et Li sp. nov., A. maechamensis Li et Li sp. nov., A. menglaensis Li et Li sp. nov., A. naphongensis Li et Li sp. nov., A. natmataungensis Li et Li sp. nov. (male only), A. phadaengensis Li et Li sp. nov., A. shanhu Li et Li sp. nov., A. suayaiensis Li et Li sp. nov. (male only), A. tadetuensis Li et Li sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 1,364 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In other words, FA refers to small random morphological fluctuations around a symmetric mean [3,5,38,97,98]. FA incidence, relation to environmental factors, and its influence within populations has been studied on some Lycosidae and Pholcidae [17][18][19][20][21]. Here we found that some cases, like the hahniid Neoanthistea, some more lycosid, oonopid, and telemid genera (mentioned as FA?…”
Section: Fluctuating Asymmetry (Fa)mentioning
confidence: 64%
See 3 more Smart Citations
“…In other words, FA refers to small random morphological fluctuations around a symmetric mean [3,5,38,97,98]. FA incidence, relation to environmental factors, and its influence within populations has been studied on some Lycosidae and Pholcidae [17][18][19][20][21]. Here we found that some cases, like the hahniid Neoanthistea, some more lycosid, oonopid, and telemid genera (mentioned as FA?…”
Section: Fluctuating Asymmetry (Fa)mentioning
confidence: 64%
“…Similarly, the great intraspecific variation observed in the female genitalia of some sicariids [19,78], range from asymmetries in number, size and shape of spermathecae to almost symmetric structures. This suggests that asymmetries in this family and similar cases in the ochyroceratid Althepus [18,72] might be fluctuating. A few species that show AS (Scotinella britcheri and S. fratella) and all species with CA (Cithaeron praedonius, Jacaena mihun, among others) also have a range of morphological variation in female internal genitalia within the population.…”
Section: Fluctuating Asymmetry (Fa)mentioning
confidence: 90%
See 2 more Smart Citations